TRANSFORMASI SISTEM PENDAFTARAN SANTRI BARU DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM (Studi Penelitian di LPI Dayah Mudi Mesjid Raya Samalanga) - Muktar Muktar; Amiruddin Amiruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The impact of the COVID-19 outbreak has changed social and educational fabrics. The disaster changed the new student registration system of Dayah MUDI Mesjid Raya from using a manual system to an online system. However, this change has reaped many obstacles in society, where today's technological developments have not yet entered all levels of society. So this is a big obstacle in the transformation of the new student registration system of Dayah MUDI Mesjid Raya Samalanga. Although there are many obstacles in the field, the dayah still tries to carry out an online registration system, even though they have to manually serve a small part of the registrant students. Although there are still many shortcomings in its management, the dayah has compiled guidelines and an implementation team in a good and orderly manner. This research includes qualitative research with data collection methods through observation, interviews and documentation. The results showed that the new student registration model during the transformation of the new student registration system of MUDI Mesjid Raya Samalanga was following the flow of technology, namely online registration, where the internet became the main capital in the problem of registering new students. For those who register new students must fill out the online form / google form. Through the website www.mudimesra.com all requirements and procedures can be accessed. The quality of education at this institution has raised the standard from the admission of regular regular students who study the books of grade 1 in grade 1, now grade 2 books are directly studied in grade 1. So that the ability of the santri increases compared to the ability of the santri in other salafiyah dayah in Aceh.